PTH-052 How The New Inflammatory Bowel Disease Registry And Patient Management System (ibd-r/pms) Has Help Define The Future Of Our District General Ibd Service. (9th June 2014) - Johnson, MW; Lithgo, K; Price, T
Abstract : Introduction: In 2013 the Luton and Dunstable (LandD) University Hospital, became the first hospital in UK to pilot the new IBD-R/PMS. The PMS was designed by clinicians to be quick and easy to use, at the point of care, to facilitate best clinical practice. The system is live with PAS details, accessible throughout the Trust and provides up-to-date information consolidated in one place with real-time data collection. The IBD-Registry aims to provide the UK with its first ever national IBD statistics, by pooling some of this anonymised data centrally. Objective: To reviewed the effects of IBD-R/PMS on a DGH's IBD Service. Methods: The LandD looks after 2780 IBD patients. Data from 2571 of these patients has been uploaded, with pre-existing data on 1200 being ported over from an old Rotherham database. The IBD-R/PMS can analyse the service and individuals workloads, to help provide service reports and evidence of self worth for the IBD nurse specialists role. The new National IBD Standards (E2) advocates the use of electronic clinical management systems. When patients phoned up "out of the blue", clinical staff can quickly access clinical summary sheets, just by using a name search. To-date we have had no complaints or concerns about data inputting or security issues. Instead patients felt reassured and confident that staff were well informed about their condition. The instant generated clinic letters have been a particular success with both patients and GPs. Results: The dashboard facility gives an instant overview of our local IBD cohort, revealing 2571 (as of Jan 2014), 1280 with UC, 934 with Crohn's, 77 with IBD unclassified and 59 with microscopic colitis. It takes 4–5 min to upload the basic details in clinic, although complex histories take longer. There were 1072 telephone and virtual clinic contacts recorded between Jan-Nov 2013. The time spent on the IBD phone line was 943 min, with a further 940 min spent dealing with these issues. This work saved 149 clinic visits. Data reports sent to our CCG provided evidence of this service and enabled an income generation not previously claimed for. The IBD-R/PMS identified 913 clinic visits and 173 inpatient reviews. Experience using the worklist functions now allow us to better monitor colonoscopy surveillance, schedule MDT patients and regulate azathioprine reviews. Conclusion: The IBD-R/PMS has been a huge success, with relatively little effort on our behalf. It would be difficult now to go back to paper based reporting. There are still benefits yet to be fully appreciated. The service reports have been easy to generate and strongly assisted in our bid to fund 2 additional IBD nurses. Further integration is expected to reduce duplication with our own IBD-SSHAMP project, IBD-GRS and the Biologics Audit. Disclosure of Interest: None Declared.